2013
DOI: 10.1590/0074-0276130293
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the pandemic norovirus variant GII.4 Sydney 2012 in Rio Branco, state of Acre, northern Brazil

Abstract: Noroviruses (NoVs) are important cause of gastroenteritis in humans worldwide. Genotype GII.4 is responsible for the majority of outbreaks reported to date. This study describes, for the first time in Brazil, the circulation of NoV GII.4 variant Sydney 2012 in faecal samples collected from children aged less than or equal to eight years in Rio Branco, state of Acre, northern Brazil, during July-September 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…In the present study, the frequency observed (4.7%) was lower than that observed in Rio de Janeiro (13.5%) and São Paulo (28.2%), but similar to the 3.9% and 5.4% found in Belém, which is also in the Amazon Region. In Rio Branco City, few studies have been performed involving only NoV genotyping characterization, reinforcing the importance of the data presented herein.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the present study, the frequency observed (4.7%) was lower than that observed in Rio de Janeiro (13.5%) and São Paulo (28.2%), but similar to the 3.9% and 5.4% found in Belém, which is also in the Amazon Region. In Rio Branco City, few studies have been performed involving only NoV genotyping characterization, reinforcing the importance of the data presented herein.…”
Section: Discussionmentioning
confidence: 61%
“…Among these we can highlight: NoV infections in Belém (inpatients: 36.5%), NoV in cruise ships (outbreak: 3%), outbreak of acute diarrheal disease in Paraíso do Tocantins (4%), infections among hospitalized children in Porto Velho (7.8%), detection of a recombinant GII.7/GII.20 strain in an African‐descendant community (19.7%), and NoV in high prevalence among sporadic cases in Manaus (35.2%) . NoV was previously reported in Rio Branco, Acre, in two situations; detection of genotypes GII.16 and GII.17 in a study involving Brazil states, as well as the first description of the GII.4 Sydney variant in Brazil …”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, GII.4 NoV is most frequently reported from emergency departments [5,6,29,30]. The presence of a variety of genotypes in Sergipe and the periodic shift of GII.4 variants (i.e., GII.4 New-Orleans_2009 and GII.4 Sydney_2012) reflects the emergence worldwide of GII.4 variants [29,[31][32][33][34][35][36], confirming that the NoV genotypes have a wide geographical distribution. The increased detection of GII.4 could be explained by GII.4 theoretically causing more severe disease than other genotypes [31,37], but GII.4 diarrhoea severity in our patients was similar to other genotypes and we do not have evidence of an increased severity.…”
Section: Discussionmentioning
confidence: 93%
“…A recent report demonstrated this variant as circulating in Northern Brazil, causing sporadic cases in hospitalized children [41]. This strain also became the predominant NoV variant in the USA in 2012/2013, but its emergence was not associated with an increase in the activity of outbreaks when compared to previous seasons [63].…”
Section: Discussionmentioning
confidence: 95%